Design of a Portable Air Quality Monitoring System Using Internet of Things Based Multisensor - Mona Berlian Sari; Dani Kurniawan (International Journal of Applied Sciences and Smart Technologies, 2026)
The rise in air pollution in the modern era, particularly in urban areas, has hurt public health. Current conventional systems can only measure a limited number of parameters. While several air quality monitoring systems exist, they are extremely expensive and therefore inaccessible to the general public. The objective of this system is to monitor air quality by detecting harmful gases and fine particles in indoor air at a low cost. This system uses a multisensor setup consisting of a DHT11 sensor, an MQ-135 sensor, and a GP2Y1010AU0F sensor to measure temperature, humidity, CO gas levels, and fine particle levels in the air. The method applied is an engineering research approach to design a portable air quality monitoring system. The result of this research is a portable air quality monitoring system based on the Internet of Things. The results of the characterization tests for each sensor in the system indicate that the system can measure the parameters accurately. The DHT11 sensor has a coefficient of determination of 0.998 and 0.998, the MQ-135 sensor has a coefficient of 0.986 and 0.957, and the GP2Y1010AU0F sensor has a coefficient of 1. Based on the regression equations obtained, the performance of the DHT11, MQ-135, and GP2Y1010AU0F sensors indicates that they can effectively respond to changes in temperature, CO levels, and dust levels occurring in the environment.